Alterações cardiovasculares induzidas pela administração aguda e crônica do protótipo de fármaco LQFM-21 - Trindade, Neidiane Rosa (2015)
This study aimed to investigate the effects hypotensive (LQFM-21), trying to identify a pharmaceutical potential for this new drug prototype. Male Wistar spontaneous hypertensive rats (SHR) and wistar rats were used to evaluate the effect of LQFM-21 on mean arterial pressure (MAP), heart rate (HR), renal vascular conductance (RVC), arterial vascular conductance (CVA) and baroreflex sensitivity index (BI). The administration of LQFM-021 (0.05, 0.1, 0.2, 0.4 mg / kg, iv.) Decreased MAP (-9.0 ± 1.4, -21.5 ± 2.9, ± 2.8 - 26.7 mmHg respectively); increased RVC (12.0 ± 1.9, 23.2 ± 3.2, 26.8 ± 6.3, 34.8 ± 5.9%, respectively) and CVA (17.3 ± 1.7; 27 8 ± 2.6, 32.7 ± 4.8 and 42.2 ± 3.4%, respectively) in anesthetized normotensive rats. In SHR, also found reduction of MAP (-16.9 ± 2.8; -19.4 ± 2.5; -22.0 ± 3.8 -17.2 ± 6.4 mmHg, respectively), HR (-11.2 ± 0.8 bpm at a dose of 0.04 mg / kg) and an increase in RVC (22.2% at a dose of 0.2 mg / kg) and CVA (12.2 (12.2 ± 2.1, 13.8 ± 5.6, 18.2 ± 2.3, 15.6 ± 3.1% at doses of 0.05, 0.1, 0.2, 0.4 mg / kg, respectively). Both the acute, oral as the oral administration chronicle of LQFM-21 at a dose of 15 mg / kg reduced the MAP in animals wistar 89.9 ± 1.9 mmHg and 136.4 ± 4.9 mmHg SHR without changing BI in wistar animals with the infusion of phenylephrine -2.3 ± 0.32 vs 1.9 ± 0.1 mmHg / bpm and SHR -1.9 ± 0.2 vs. -1.9 ± 0.3 mmHg / bpm, with infusion nitroprusside in wistar 3.2 ± 0.31 vs 3.0 ± 0.04 bpm / mmHg and 3.9 ± 0.6 vs SHR 3.0 ± 0.04 bpm / mmHg. Together our results demonstrated hypotensive effects of LQFM- 21. However further studies are needed to identify the mechanism of action and toxicity of this drug prototype.